High-throughput and tunable synthesis of colloidal CsPbX3 perovskite nanocrystals in a heterogeneous system by microwave irradiation. Issue 71 (22nd August 2017) - Long, Zi; Ren, Hong; Sun, Jianghui; Ouyang, Jin; Na, Na
Abstract : A high-throughput and controllable synthesis of colloidal CsPbX3 perovskite NCs with tunable properties and morphologies was achieved by microwave irradiation within minutes. Abstract : By simple microwave irradiation, a high-throughput, single-step, rapid but controllable synthesis of stable colloidal CsPbX3 perovskite NCs with tunable properties and morphologies (nanocubes, nanorods, nanowires, quadrate nanoplates and hexagonal nanoplates) was achieved. It was employed in a heterogeneous solid–liquid reaction system within minutes without any tedious pre-preparation.